A scale-up evaluation of a semicontinuous culture of Scenedesmus sp. in a raceway under greenhouse conditions using a commercial fertilizer as culture medium. Issue 10 (26th November 2021) - Fernández-Linares, Luis; Durán-Páramo, Enrique; Guerrero-Barajas, Claudia
Abstract: In the present work, Scenedesmus sp. was grown under a semicontinuous regime in fertilizer (Bayfolan® Forte, 1 mL L −1 ) medium, and Bold's Basal Medium (BBM) as control, in raceways of 200 and 2000 L under greenhouse conditions. The biomass, lipid, protein, carbohydrate and total pigment production was determined. The culture under the semicontinuous regime allowed an increase in the productivities in each consecutive cycle, reaching a lipid productivity of 20.00 ± 6.29 mg L −1 d −1 in Bayfolan medium. The biomass productivity in the medium supplemented with fertilizer was significantly higher than in the BBM. The protein productivity was significantly higher in Bayfolan (1.93 ± 0.28 L −1 d −1 ). The average carbohydrate productivity of the cycles was 10.10 ± 2.01 mg L −1 d −1 . The fertilizer allowed an increase of up to 3-fold in total pigment productivity compared to the BBM. The fatty acids obtained were mainly composed of C16:0, C18:3n3 (α-linolenic) and C18:0. Palmitic acid (C16:0) was the main fatty acids methyl ester accumulated along with stearic (C18:0) and myristic (C14:0) acids. It was shown that the utilization of the liquid fertilizer Bayfolan is a potential alternative to replace conventional media.